ANALYSIS OF COMMUNITY EMPOWERMENT STRATEGIES FOR COASTAL COMMUNITY POWER IN INDONESIA MARINE SCHOOL PROGRAM - Sayidah, Nur; Wardhono, Hendro; Marwiyah, Siti (Advances in Social Sciences Research Journal, 2022)
The activities of community empowerment through marine schools realize the power of coastal communities. Power refers to two keywords, namely surviving and rising again. When a person and society is in a disaster-affected area, they can plan, organize, and implement the stages of rescue. This ability is beneficial both for themselves and or their community. They can avoid disasters that occur and can generally live again. The implementation of the marine school program has opened a discourse and a spectrum of thought that provides space for community empowerment activities in coastal areas. Improvement of program performance and sustainability is essential to be studied. The paper analyzes community empowerment strategies based on enabling, empowering, and protecting activities. The implementation of these activities pays close attention to the locality in the community, including local issues, local autonomy, and local accountability.